The Transformation of Agriculture, Forestry and Fisheries Sectors in the Indonesian Economy - Abi Pratiwa Siregar; Edy Rahmantyo Tarsilohadi; Nadia Oktaviana (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
As time goes by, the role of the agriculture, forestry and fisheries sectors in the Indonesian economy tended to decrease. This was inseparable from the development of industrialization and digitalization. However, it was difficult to find studies that provide information on how much this transformation happened, especially at the provincial level. Therefore, this research aims to determine how much the shifting in the agricultural, forestry and fisheries sectors in each province so that describe the sectoral transformations that occurred at the national level. The basic method in this research was descriptive analytical using secondary data from the Central Bureau of Statistics from 2010 to 2019. The analytical tools that used were Location Quotient (LQ) and Dynamic Location Quotient (DLQ), and shift share analysis. The results showed that more than fifty percent of the total 34 provinces in Indonesia relied on the non-agricultural sector. Nationally, the agriculture, forestry and fisheries sectors ranked fourth after the manufacturing, wholesale and retail industries; auto and motorcycle repair, and construction. In response to this, it was necessary to increase land productivity and increase the capacity of human resources in a sustainable manner. This aimed to maintain food security and prepare human resources to be more skilled in order to adapt to the shifting economic structures.